Integration of Sharia Financial Literacy and Brand Happiness in Sharia Cooperatives: A Study of Member Behavior and Its Impact on Improving Welfare - Elman Nafidzi; Nuur Halimatus Sa’adiah Binti Masrukhi; Khabib Musthofa; Ismi Audina (Faculty of Economics and Management, 2026)
The transformation in the financial behavior of Islamic cooperative members has become a crucial issue amid growing public demand for Islamic value-based financial services. Islamic financial literacy and emotional experiences with cooperative brands are believed to play a significant role in shaping economic behavior and improving members' psychological well-being. This research is motivated by the need to understand how these two variables interact and how economic behavior functions as a mechanism linking changes in member well-being. The purpose of this study is to analyze the influence of Islamic financial literacy and brand happiness on economic behavior, and to investigate their impact on the psychological well-being of members of Islamic cooperatives. The research used a mixed-methods approach, employing Partial Least Squares structural analysis to quantitatively examine relationships among variables, while qualitative data provided support to enrich the interpretation of the findings. The results show that Islamic financial literacy has the greatest influence on economic behavior, while brand happiness makes a significant direct contribution to improving psychological well-being. Economic behavior was also shown to partially mediate the relationship between literacy and brand happiness with psychological well-being, confirming that changes in well-being are influenced not only by knowledge and emotions, but also by established economic habits. Quantitatively, the SEM-PLS model confirmed that the path coefficient for Islamic financial literacy was the strongest, with the highest significance value. All indicators were tested for validity and reliability using outer and inner models, which showed satisfactory results. This study concludes that integrating literacy and brand happiness is a crucial strategy for advancing Islamic cooperatives, introducing a conceptual model that combines cognitive, affective, and behavioral aspects to explain psychological well-being more comprehensively.